Production, isolation and characterization of radiochemically pure 163Ho samples for the ECHo-project - Dorrer, Holger; Enss, Christian; Gastaldo, Loredana; Velte, Clemens (Radiochimica acta, 2018)
Several experiments on the study of the electron neutrino mass are based on high-statistics measurements of the energy spectrum following electron capture of the radionuclide 163Ho. They rely on the availability of large, radiochemically pure samples of 163Ho. Here, we describe the production, separation, characterization, and sample production within the Electron Capture in Holmium-163 (ECHo) project. 163Ho has been produced by thermal neutron activation of enriched, prepurified 162Er targets in the high flux reactor of the Institut Laue-Langevin, Grenoble, France, in irradiations lasting up to 54 days. Irradiated targets were chemically processed by means of extraction chromatography, which allowed separating the formed Ho from the 162Er target-material and from the main byproducts 170Tm and 171Tm, which are co-produced in GBq amounts. Decontamination factors of >500 for Er and of >105 for Tm and yields of 3.6·1016 and 1.2·1018 atoms of 163Ho were obtained, corresponding to a recovery yield of 95 % of Ho in the chemical separation. The Ho-fraction was characterized by means of γ-ray spectrometry, Inductively-Coupled-Plasma Mass Spectrometry (ICP-MS), Resonance Ionization Mass Spectrometry (RIMS) and Neutron Activation Analysis (NAA). In this process, the thermal neutron capture cross section of 163Ho was measured to σHo-163 to Ho-164m= (23±3) b and σHo-163 to Ho-164g= (156±9) b for the formation of the two isomers of 164Ho. Specific samples were produced for further purification by mass separation to isolate 163Ho from the Ho-isotope mixture, as needed for obtaining the energy spectrum within ECHo. The partial efficiency for this second separation step is (32±5) %.